ANTIBIOTIC RESIDUE LEVELS IN CAMEL, CATTLE AND SHEEP TISSUES USING LC-MS/MS METHOD - W. R. El-Ghareeb; Z. Sh. Mulla; A. M. A. Meligy; W. S. Darwish; A. M. Edris (Journal of Animal and Plant Sciences, 2019)
Antimicrobials are very essential in prevention and control of infectious diseases for both humans and animals. However, the unregulated use of the antimicrobials may lead to several adverse health effects, such as development of multidrug resistant microbial strains, allergic and anaphylactic reactions. Saudi Arabia is one of the major countries in Middle East and Arabian Peninsula with a drastic increase in the livestock production. However, there is a clear lack of information about the current situation of antimicrobial residues in meat and edible offal intended for human consumption in Saudi Arabia. Therefore, this study screened the residue levels of nine antimicrobials with the most common use in Saudi Arabia veterinary medical field. These antimicrobials were enrofloxacin, ciprofloxacin, tylosin, erythromycin, tetracycline, oxytetracycline, chlortetracycline, sulfamethazine and sulfaquinoxaline. The tested samples included muscles, livers and kidneys of camel, cattle and sheep slaughtered at Al-Ahsa, Saudi Arabia. Antimicrobial residues in the tested samples was quantitatively estimated using liquid chromatography tandem mass spectrometry (LC–MS/MS). Sulfamethazine was detected at higher levels compared with the maximum residual limits (MPL) established by the regulatory authorities. Therefore, the effect of different cooking methods on sulfamethazine residues was investigated. The achieved results indicated occurrence of antimicrobial residues in the examined samples at levels below the recommended MPL, except for sulfamethazine that was detected at higher levels. Six antimicrobial residues were detected in samples collected from sheep; however, only three antimicrobials were detected in camel and cattle. Efficient heat treatment of the meat contaminated with sulfamethazine significantly reduced the residue load of sulfamethazine. In conclusion, efficient cooking of meat and observing the withdrawal periods of different antimicrobials are advisable to reduce human exposure to antimicrobial residues via meat consumption.
Keywords: Camel; Cattle; Sheep; tissues; LC-MS/MS; antimicrobials